Leukocytosis as a Predictor of Clinical Worsening and Complications in Children with Pertussis: A Systematic Review of Case Study - Bakhtiar Bakhtiar; Inayah Zhiaul Muttaqin; Ghazi Maulana; Ghina Tsurayya; Garsia Safana (Poltekkes Kemenkes Palu, 2023)
Pertussis is a highly contagious disease with clinical features ranging from mild to severe and various complications. Hematological examination, especially the leukocyte count, can predict the possibility of clinical deterioration with several complications, such as pneumonia. This case study aimed to assess whether leukocytosis could indicate the clinical worsening of pertussis in children. This research method is a systematic review on a case study. The subject of this case study is a child with pertussis experiencing clinical deterioration. Prominent laboratory data in this case study includes leukocytosis. This systematic review aims to analyze the association between leukocytosis and the clinical deterioration of this case study. Literature search procedure using PubMed, Cochrane, and Google Scholar search instruments. The keywords used are